2014
DOI: 10.1007/s10517-014-2717-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Mitochondrial Superoxide Dismutase-2 Gene in Adolescents with Essential Hypertension

Abstract: The study of LPO processes in adolescents of different races with essential hypertension revealed that Mongoloids exhibit oxidative stress by altering the level of the formation of diene conjugates, the primary LPO products. Caucasians increased the levels of both primary and end products of LPO, diene conjugates, and malondialdehyde. The revealed differences can be genetically determined because ethnic differences in the frequency of SOD2 gene Ala16Val polymorphism and its contribution to the biochemical phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 4 publications
0
9
0
5
Order By: Relevance
“…Thus, we suggest that dysfunction between ROS and antioxidant capacity may be more pronounced in the ventral medulla, which contributes, in part, to the development of sympathetic overactivation and hypertension observed in rats exposed to protein restriction during pregnancy and lactation. Interestingly, clinical studies have shown that lipid peroxidation (MDA levels) is augmented in blood of patients with essential hypertension, and at the same time, SOD and CAT activities are reduced in these patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we suggest that dysfunction between ROS and antioxidant capacity may be more pronounced in the ventral medulla, which contributes, in part, to the development of sympathetic overactivation and hypertension observed in rats exposed to protein restriction during pregnancy and lactation. Interestingly, clinical studies have shown that lipid peroxidation (MDA levels) is augmented in blood of patients with essential hypertension, and at the same time, SOD and CAT activities are reduced in these patients …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, clinical studies have shown that lipid peroxidation (MDA levels) is augmented in blood of patients with essential hypertension, and at the same time, SOD and CAT activities are reduced in these patients. 40,41 Previous studies have suggested that oxidative stress in the dorsal medulla (or specifically in nucleus tractus solitarii), it may be associated with hypertension model in which there depression of the baroreflex. 14 Interestingly a recent study demonstrated that the hypertension in rat offspring subjected to perinatal protein malnutrition is not related to the baroreflex dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…У под-ростков с лабильной артериальной гипертензией окислительный стресс формируется за счет ин-тенсификации процессов ПОЛ на стадии образо-вания кетодиенов (КД) и сопряженных триенов (СТ), а в группе со стабильной артериальной ги-пертензией -на стадии образования первичных продуктов -диеновых конъюгатов (ДК) и конеч-ных продуктов ПОЛ [68]. Значимыми явились также данные об ýтногенетической детерминиро-ванности окислительного стресса при формиро-вании ýссенциальной артериальной гипертензии у детей (в группе подростков-бурят коýффициент окислительного стресса оказался равным 2,60, что было ниже, чем у русских -5,31) [69].…”
Section: обзоры и лекцииunclassified
“…Дисбаланс этой системы сопровождает или является причиной более двухсот заболеваний у человека [7,13].…”
Section: Discussionunclassified